2003
DOI: 10.1038/sj.bmt.1704165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transplanted dose of CD56+ cells on development of graft-versus-host disease in patients receiving G-CSF-mobilized peripheral blood progenitor cells from HLA-identical sibling donors

Abstract: We investigated effects of variations in the cellular composition of G-CSF-mobilized peripheral blood progenitor cell (G-PBPC) allografts on clinical outcomes of allogeneic PBPC transplantation. We retrospectively analyzed transplanted doses of various immunocompetent cells from 27 HLA-identical sibling donors in relation to engraftment, incidence of graft-versus-host disease (GVHD), and survival. Significant variability was documented in both absolute numbers and relative proportions of CD34+, CD2+, CD3+, CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
3
26
1
1
Order By: Relevance
“…The role of NK cells and their alloreactivity in allogeneic hematopoietic SCT (allo-HSCT) is currently controversial for different transplant settings. 1,[9][10][11][12][13][14] Our earlier study confirmed the deleterious role of a killer Ig-like receptor (KIR) ligand mismatch in this haploidentical GIAC protocol. 15,16 A further study also showed that the recovery of NK cells is, and can be used as, an indicator of the clinical outcome after unmanipulated haploidentical transplantation.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The role of NK cells and their alloreactivity in allogeneic hematopoietic SCT (allo-HSCT) is currently controversial for different transplant settings. 1,[9][10][11][12][13][14] Our earlier study confirmed the deleterious role of a killer Ig-like receptor (KIR) ligand mismatch in this haploidentical GIAC protocol. 15,16 A further study also showed that the recovery of NK cells is, and can be used as, an indicator of the clinical outcome after unmanipulated haploidentical transplantation.…”
Section: Introductionsupporting
confidence: 54%
“…9,17 However, no data are currently available on the role of NK dose or its subsets in the grafts after unmanipulated haploidentical transplantation. Yamasaki et al 13 showed earlier that the CD16 þ CD56 þ cell dose is inversely correlated with the incidence of GVHD when they studied 27 patients who received PBSCs from HLAidentical sibling donors, suggesting an important role for NK cells in the development of GVHD. This was confirmed by Kim et al 14 in 61 patients receiving G-CSF-mobilized PBSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the reported effects of NK- 8 and B-cell 28 doses are either relatively small or not confirmed in all studies, and this was also the case in our study. Our results are also in agreement with several other reports showing that the dose of T cells, the undisputed and most powerful effectors of aGVHD, does not predict risk of aGVHD.…”
Section: Discussionmentioning
confidence: 39%
“…7 Because T-cell depletion of the graft is also associated with an increased risk of leukemia relapse and infections, research has also focused on identifying other cellular components of the graft that affect the incidence and severity of aGVHD. Indeed, the effect of the graft content of several immune effectors such as T, NK 8 and more recently B cells 9 as well as of the CD4 ϩ CD25 hi FoxP3 ϩ T regulatory cells (Tregs) 10,11 on the risk of aGVHD has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Higher CD34 ϩ cell doses have been shown to correlate with more frequent chronic GVHD (cGVHD) following myeloablative AHCT, although several recent studies dispute this prognostic connection. [4][5][6][7] The influence of graft composition on clinical outcomes after reduced-intensity conditioning is less well-characterized. With emphasis shifting from myeloablative chemoradiation toward alloimmune effects of the graft, an understanding of the relationships, if any, between donor graft cell subpopulation contents and various outcomes may be particularly important.…”
Section: Introductionmentioning
confidence: 99%